Der "wandernde" Strom.: Studien zur Talgeschichte des Indus - Wilhelmy, Herbert (ERDKUNDE, 1966)
Frequent shifts in course are a characteristic feature of the Indus and its tributaries. The Pleistocene delta fans of the Punjab and the alluvial flats of the Sind are interlaced by old stream beds with deserted settlements along their edges. Lines of abandoned hilltop town sites reveal that they once lay along a river bank. Elongated depressions whose green cultivated plots stand out against the barren landscape, chains of salt lakes and meander elbows which are dried up or filled with stagnant water confirm the observation already made by early travellers, that the rivers of the Indus lowland invariably shift to the right. One can, in fact speak of a law of westward stream migration. Two principal tasks face the researcher in historical geography. On the one hand, by means of traceable former stream courses, to locate settlement sites for which literary evidence exists; on the other, with the help of settlement sites which are archaeologically evident on the ground, to reconstruct the courses of individual streams. In this paper, the author seeks to make such a contribution.